2022
DOI: 10.3389/fgene.2022.976356
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypoxia-driven gene signature that can predict the prognosis and drug resistance of gliomas

Abstract: Hypoxia spontaneously forms in the interior of glioma tissues and regulates the expression of various genes. However, the status of hypoxia-driven genes in glioma tissues is not completely known. In the current study, RNA-seq data of 695 glioma tissues in The Cancer Genome Atlas (TCGA) were set as a discovery cohort and were used to identify hypoxia-driven genes and construct a novel gene signature. The prognostic values of that signature were verified in data from the TCGA and the Chinese Glioma Genome Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A cuproptosis-related prognostic signature consisting of MAGEA6 and EPO promotes HCC development (44). A correlation was observed between CFHR3 and hypoxia (45). The level of FTCD served as a powerful diagnostic predictor for distinguishing early-stage HCC from benign tumors (36).…”
Section: Discussionmentioning
confidence: 99%
“…A cuproptosis-related prognostic signature consisting of MAGEA6 and EPO promotes HCC development (44). A correlation was observed between CFHR3 and hypoxia (45). The level of FTCD served as a powerful diagnostic predictor for distinguishing early-stage HCC from benign tumors (36).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-response genes, such as hypoxia-inducible factor HIF-2α and VEGF, are highly expressed in GSCs. Intriguingly, two reports have demonstrated that hypoxia-associated transcriptional signatures can be used as prognostic markers for glioblastoma patients [ 43 , 44 ] .…”
Section: Common Drug Resistance Mechanisms In Brain Cancersmentioning
confidence: 99%